developing Developing EFL Writing Materials Using Graphic Organizers At English Department of IAIN Palangka Raya - Sabarun Sabarun (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
The study attempted to develop a syllabus and instructional materials that appropriate for the teaching of Essay Writing course Using Graphic Organizers. The Research and Development (R&D) procedure was employed in this study. The model used for designing the syllabus and developing instructional materials followed Yalden’s model known as Language Program Development with modification. The subjects of the study were the 48 students, the coordinator of English Study Program at IAIN Palangka Raya, and Essay Writing lecturer. The final product of this study is the instructional materials for nine meetings covering introduction to the essay (unit 1 meetings 1-4), illustration essay (unit 2 meeting 5), classification essay (unit 3 meeting 6), process essay (unit 4 meeting 7), comparison contrast essay (unit 5 meeting 8), and cause and effect (unit 6 meeting 9). Each unit consisted of learning objective, topic, sub-topic, description, relevancy, and keywords. The instructional material has been empirically tested in try-out stage. Based on the statistical calculation, it was shown that using proposed instructional materials gave facilitative effect on the students’ essay writing performance. Here, the t value of 8.639 was greater than t theoretic at the 5% (1.648) and 1% (2.423) of significant level.